2024
DOI: 10.3390/foods13040556
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Acrylamide: A Detailed Review on Formation, Detection, Mitigation, and Its Health Impacts

Indira Govindaraju,
Maidin Sana,
Ishita Chakraborty
et al.

Abstract: In today’s fast-paced world, people increasingly rely on a variety of processed foods due to their busy lifestyles. The enhanced flavors, vibrant colors, and ease of accessibility at reasonable prices have made ready-to-eat foods the easiest and simplest choice to satiate hunger, especially those that undergo thermal processing. However, these foods often contain an unsaturated amide called ‘Acrylamide’, known by its chemical name 2-propenamide, which is a contaminant formed when a carbohydrate- or protein-ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 113 publications
0
4
0
Order By: Relevance
“…In animal experiments, the toxicity is induced due to saturation of the detoxification mechanisms as well as not all the damages are repaired since the reparative capacity is exceeded. As suggested in some previous research, vitamins and bioactive substances in food might also play a protective role in humans ( 10 ).…”
mentioning
confidence: 68%
“…In animal experiments, the toxicity is induced due to saturation of the detoxification mechanisms as well as not all the damages are repaired since the reparative capacity is exceeded. As suggested in some previous research, vitamins and bioactive substances in food might also play a protective role in humans ( 10 ).…”
mentioning
confidence: 68%
“…This evidence supports our finding that additional consumption of grilled and fried foods during early pregnancy, which increases the intake of exogenous dietary AGEs, could be harmful to human embryos. Apart from AGEs, undesirable byproducts of thermal processing include acrylamide and heterocyclic aromatic amines, which are putative sources of cardiovascular toxicity, reproductive toxicity, teratogen, carcinogenicity, and neurotoxicity [47,48]. In contrast to the harmful effects of unhealthy foods, we identified the probable protective dietary factors of VSD, including fish and shrimp (OR = 0.42), fresh eggs (OR = 0.58), soy products (OR = 0.69), and dairy products (OR = 0.71), consistent with our previous publication [13].…”
Section: Discussionmentioning
confidence: 99%
“…The development of analytical methods, e.g., high-performance liquid chromatography (HPLC), gas chromatography (GC) with mass spectrometry (MS) detection, or in the selected ion monitoring (SIM) mode, or tandem mass spectrometry (MS/MS) in the multiple reaction mode (MRM) with isotope-labelled standards, enabled accurate determination of ACR content in individual food products, which made it possible to monitor the ACR level in ready products by food manufacturers [27,28]. According to the Joint Expert Committee for Food Additives (a UN Food and Agriculture Organization and World Health Organization advisory body), the main ACR sources in the diet contributing to the total ACR intake are chips (16-30%), potato crisps (6-46%), roasted coffee (13-39%), cakes, and cookies (10-20%), as well as various kinds of bread (10-30%) [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Relative to their body mass, their estimated daily intake of ACR is three times higher than that of adults [28,33]. The research conducted during the past 20 years has shown that consumption of ACR-containing products leads to disorders in human and animal organisms [6][7][8][9][10][11]21,22,27,33]. This effect is strictly dependent on the ACR dose, time of exposure to ACR, and the species of animals used in the experiment.…”
Section: Introductionmentioning
confidence: 99%